Deficiency in ST6GAL1, one of the two α2,6-sialyltransferases, has only a minor effect on the pathogenesis of prion disease - Makarava, Natallia; Katorcha, Elizaveta; Chang, Jennifer Chen-Yu; Lau, Joseph T. Y.; Baskakov, Ilia V. (Frontiers in Molecular Biosciences, 2022)
Abstract Prion diseases are a group of fatal neurodegenerative diseases caused by misfolding of the normal cellular form of the prion protein or PrPC, into a disease-associated self-replicating state or PrPSc. PrPC and PrPSc are posttranslationally modified with N-linked glycans, in which the terminal positions occupied by sialic acids residues are attached to galactose predominantly via 2-6 linkages. The sialylation status of PrPSc is an important determinant of prion disease pathogenesis, as it dictates the rate of prion replication and controls the fate of prions in an organism. The current study tests whether a knockout of ST6Gal1, one of the two mammalian sialyltransferases that catalyze the sialylation of glycans via 2-6 linkages, reduces the sialylation status of PrPSc and alters prion disease pathogenesis. We found that a global knockout of ST6Gal1 in mice significantly reduces the α2-6 sialylation of the brain parenchyma, as determined by staining with Sambucus Nigra agglutinin. However, the sialylation of PrPSc remained stable and the incubation time to disease increased only modestly in ST6Gal1 knockout mice (ST6Gal1-KO). A lack of significant changes in the PrPSc sialylation status and prion pathogenesis is attributed to the redundancy in sialylation and, in particular, the plausible involvement of a second member of the sialyltransferase family that sialylate via 2-6 linkages, ST6Gal2.